Kinerja Baitul Maal Wa At-Tamwil Umat Mandiri-Pesantren Hidayatullah Balikpapan Menggunakan Maslahah Performa - M. Rizky Kurnia Sah; Achmad Firdaus; Mukhammad Yasid (Al-Tijary, 2021)
This research generally describes the application of performance measurement in Baitul Maal wat Tamwil (BMT) based on orientation to benefit all stakeholders (stakeholders & shareholders), but studies that specifically measure aspects of the methodology for implementing performance measurement are still limited. Therefore, Maslahah Performa is used as an instrument in the application of performance measurement in BMT Umat Mandiri. The study aims to determine the implementation of performance measurement Maslahah Performa issues on BMT Umat Mandiri. Knowing the results of the analysis of the application of process performance measurement and benefit-based performance results in BMT Umat Mandiri. The methodology used in this study is qualitative and quantitative research methods with case study design. The research findings indicate that six benefit orientations exist in BMT Umat Mandiri. These orientations include worship, internal processes, talents, learning, customers, and property. The six orientations found in this research have a foundation of benefit in realizing strategic objectives for the achievement of benefit. BMT Umat Mandiri has a process performance of 0,400 and performance results of 0,656 which means that BMT Umat Mandiri provides less benefit to stakeholders.